Relationship of Personality Traits Hexaco and Self Esteem in University Students - Javed, Rema; Aks, E-Noor; Ramzan, Faiza (2022)
Self-esteem reveals the individual’s sense of worth and the degree to which the individual values himself. It represents the individual’s general as well as personal feelings diagonally the time and context. It pertains to the personnel evaluation regarding their potential, worth, capabilities and norms. Therefore, this research was carried out to analyze the HEXACO (conscientiousness, openness, honesty-humility, extraversion, neuroticism and agreeableness) in association with the self-esteem of university students. For this purpose, 300 participants of different ages, gender, education level and residence were included in the study. The data was collected on a predesigned questionnaire and was analyzed using statistical tools. It was found that openness, conscientiousness, and self-esteem, were substantially higher (p<0.05) in males, but extraversion, agreeableness, and neuroticism were significantly higher in females (p<0.05). Honesty-humility was also higher in female students. Further evaluations revealed that openness, conscientiousness, extraversion, agreeableness, and honesty-humility were significant positive predictors (p<0.05) of self-esteem in university students, whereas neuroticism served as a significant (p<0.05) negative interpreter of self-esteem. Hence, it was concluded from this research that personality traits affect all elements of university students and are strongly associated with their self-esteem.